METODE SYSTEMATIC LITERATUR REVIEW PERKEMBANGAN START UP DIGITAL PADA ERA SOCIETY - Resnawita Resnawita; Jhon Veri (Politeknik Bisnis Indonesia, 2024)
The research aims to examine the development of digital startups in the Society era through the systematic literature review (SLR) method. The focus of this research includes dominant business models, marketing platforms used, and factors that influence the development of digital startups in Indonesia. Information was obtained from journals accessed via Google Scholar, with inclusion criteria including publications in the 2020-2023 time period, and relevance to digital startups and the Society era. Of the 40 journals found, 10 journals met the quality assessment criteria. The research results show that the dominant businesses adopted by digital startups are in the service and food sectors. Web-based platforms are the dominant ones used for marketing, followed by Android-based. The development of startups in Indonesia is increasing rapidly thanks to widespread use of the web and digitalization. However, many startups face significant challenges in the early stages, such as poor management and unsystematic operating cycles. This research emphasizes the importance of effective business strategies, such as SWOT analysis and strategic partnerships, to increase the chances of success in a competitive market. This research makes an important contribution to understanding the dynamics of digital startup development and effective digital marketing strategies.